The Influence of Learning Creativity, Learning Independence, and Emotional Intelligence on Learning Outcomes. - Cicih Nonia (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to determine the influence of learning creativity, learning independence and emotional intelligence on learning outcomes in class With an affordable population of 127 students from SMK Negeri 13 Jakarta. The sample in this study consisted of 96 respondents using proportional random sampling techniques and the Isaac and Michael formula. The data collection method in this research uses quantitative methods with survey research using questionnaires. This research uses data analysis techniques, namely regression analysis, analysis requirements testing and hypothesis testing.